Peritoneal Dialysis - Andreoli,Maria Claudia Cruz (2020)
SUMMARY Peritoneal dialysis (PD) is a renal replacement therapy based on infusing a sterile solution into the peritoneal cavity through a catheter and provides for the removal of solutes and water using the peritoneal membrane as the exchange surface. This solution, which is in close contact with the capillaries in the peritoneum, allows diffusion solute transport and osmotic ultrafiltration water loss since it is hyperosmolar to plasma due to the addition of osmotic agents (most commonly glucose). Infusion and drainage of the solution into the peritoneal cavity can be performed in two ways: manually (continuous ambulatory PD), in which the patient usually goes through four solution changes throughout the day, or machine-assisted PD (automated PD), in which dialysis is performed with the aid of a cycling machine that allows changes to be made overnight while the patient is sleeping. Prescription and follow-up of PD involve characterizing the type of peritoneal transport and assessing the offered dialysis dose (solute clearance) as well as diagnosing and treating possible method-related complications (infectious and non-infectious).